2017
DOI: 10.1186/s12916-017-0864-y
|View full text |Cite
|
Sign up to set email alerts
|

Recent household transmission of tuberculosis in England, 2010–2012: retrospective national cohort study combining epidemiological and molecular strain typing data

Abstract: Background: We estimate the proportion of tuberculosis (TB) in England due to recent household transmission, identify factors associated with being a household transmitter, and investigate the impact that identification of a case has on time to treatment of subsequent cases. Methods: TB cases notified between 2010 and 2012 in England in the same household as another case were identified; 24 locus MIRU-VNTR strain typing (ST) was used to identify household cases with likely recent transmission. Treatment delay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 17 publications
(15 reference statements)
2
20
2
Order By: Relevance
“…Similar patterns are observed in Birmingham,16 17 and in both cities, the prevalence of disease among contacts of ETB cases was higher than the prevalence of disease among migrants eligible for pre-entry screening18 and more than 10 times higher than the NICE threshold for new entrant screening 17. Additionally, studies have shown only 25% of pairs of cases sharing an address in the UK,19 and 20% of case-contact pairs in London20 had different Mycobacterium tuberculosis isolates, implying the risk of disease in household contacts is high irrespective of whether transmission has occurred. This suggests that the fact that ETB cases are not infectious may not be a valid justification for not screening their contacts.…”
Section: Introductionsupporting
confidence: 64%
“…Similar patterns are observed in Birmingham,16 17 and in both cities, the prevalence of disease among contacts of ETB cases was higher than the prevalence of disease among migrants eligible for pre-entry screening18 and more than 10 times higher than the NICE threshold for new entrant screening 17. Additionally, studies have shown only 25% of pairs of cases sharing an address in the UK,19 and 20% of case-contact pairs in London20 had different Mycobacterium tuberculosis isolates, implying the risk of disease in household contacts is high irrespective of whether transmission has occurred. This suggests that the fact that ETB cases are not infectious may not be a valid justification for not screening their contacts.…”
Section: Introductionsupporting
confidence: 64%
“…A comparison of transmission, control measures and outcomes could elucidate the difference we observed between the UK and the NL. These would include the efficiency of contact tracing in the UK [26] and the NL [27], household transmission [13], and different transmission rates between migrant groups [22].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cases infected by indistinguishable strains may be epidemiologically unrelated, due to infection with a common strain [11]. Instead, genotyping is often used to rule out transmission, for instance between household members infected with different strains [12,13]. In low incidence countries, distinguishable strains are used to estimate the fraction of cases that are not due to recent transmission, but due instead to the reactivation of existing infections or cases infected elsewhere [14].…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of transmission, control measures and outcomes could elucidate the difference we observed between the UK and the NL. These would include the efficiency of contact tracing in the UK (29) and the NL(30), household transmission (12), and different transmission rates between migrant groups (25).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cases infected by indistinguishable strains may be epidemiologically unrelated, due to infection with a common strain (10). Instead, genotyping is often used to rule out transmission, for instance between household members infected with different strains (11,12).…”
mentioning
confidence: 99%